Phytonym Study in Manuscript Usada Rare to Strengthen The Balinese Traditional Medicine System - I Nyoman Arsana; Ni Ketut Ayu Juliasih; I Putu Sudiartawan (Jayapangus Press, 2026)
The usada rare manuscript is one of the most important sources of Balinese traditional medicine, focusing on child healthcare and integrating knowledge of medicinal plants with spiritual practices. However, the plant names (phytonyms) present challenges for scientific validation, as many names are locally specific, polysemous, or refer to plant mixtures. This study aims to examine the structure and concept of usada rare, analyze phytonyms, and their relevance to modern healthcare. This study employs a qualitative-ethnographic approach through literature studies and interviews. Seven main versions of the usada rare and six supplementary lontar manuscripts containing plant name synonyms were examined. Phytonyms were extracted, cross-referenced, and matched with scientific names using ethnobotanical literature and herbarium databases. Fieldwork involved interviews with traditional healers or knowledgeable individuals. Observations and photographic documentation were used to verify plant identity and uses. Data were analyzed through editing, classification, tabulation, and interpretation, with quantitative summaries of plant part usage. A total of 275 plant species from 81 families were recorded. Fabaceae, Moraceae, and Zingiberaceae were the most represented families. Leaves were the most frequently used plant part, followed by roots and bark. Certain phytonyms, such as triketuka and sindrong, refer to herbal combinations whose full species composition remains unidentified. Overall, usada rare provides an empirical foundation for integrating local medical knowledge with contemporary, culturally sensitive approaches to child healthcare. The study also strengthens Balinese traditional medicine by reinforcing its epistemological legitimacy while opening pathways for interdisciplinary research and sustainable healthcare development.